A qualitative exploration of the sociology of poststroke visual impairments and the associated health inequalities. Issue 8 (26th June 2020) - Hanna, Kerry; Mercer, David; Rowe, Fiona
Abstract: Introduction: Inequalities have been found to exist within the visually impaired stroke population on an individual level, in relation to demographic differences, unequal access to vision services, transport, employment, and financial repercussions. The long‐term impact of living with poststroke visual impairments must be explored, in order to identify complications accessing NHS services and to inform possible changes to service planning and delivery in order to tackle such complications. Aim: To explore the extent of health inequalities within visually impaired stroke survivors in the northwest of England and discuss potential solutions to these. Methods: Focus groups and individual interviews ( n = 13 stroke survivors and n = 1 spouse) were conducted between October 2016 and January 2017. Transcription and thematic analysis of the transcripts was undertaken, using line‐by‐line coding, underpinned with social constructionism. Results: The findings draw on lived experiences of stroke survivors across their journey from prestroke to life after stroke. The three overarching experiences of stroke and visual impairment that emerged in respondent accounts were constructed in terms of "loss, " concerning (a) the physical being, (b) the psychosocial being and, (c) the systematic organization of health care. Conclusion: The stroke survivors frequently reported a complete lack of visual care, with many recounting apathetic experiences, often resonating power imbalance in the healthcare system. Where suitable care is being offered after stroke, a desire for a personalized approach to rehabilitation, with adapted communication methods specific to individual needs, featured strongly in many of the respondent accounts. The findings emphasize a need to ensure vision rehabilitation is offered to all stroke survivors suffering from poststroke visual impairment, and to educate stroke clinicians and patients of the bigger picture of life after stroke, highlighting all forms of available support. Abstract : The long‐term impact of living with poststroke visual impairments has been explored using focus groups and individual interviews, in order to identify health inequalities and potential means of addressing these. The findings emphasize a need to educate clinicians and patients of the bigger picture of life after stroke, highlighting all available support.